Incidence of biopsy-proven giant cell arteritis (GCA) in South Australia 2014–2020 - Ninan, Jem; Ruediger, Carlee; Dyer, Kathryn A.; Dodd, Thomas; Black, Rachel J.; Lyne, Suellen; Shanahan, Ernst M.; Proudman, Susanna M.; Lester, Susan; McNeil, Julian; Hill, Catherine L. (Frontiers in Medicine, 2023)
Objective To determine the incidence of biopsy proven giant cell arteritis (GCA) in South Australia. Methods Patients with biopsy-proven GCA were identified from pathology reports of temporal artery biopsies at state-based pathology laboratories, from 1 January 2014 to 31 December 2020. Incidence rates for biopsy-proven GCA were calculated using Australian Bureau of Statistics data for South Australian population sizes by age, sex, and calendar year. Seasonality was analyzed by cosinor analysis. Results There were 181 cases of biopsy-proven GCA. The median age at diagnosis of GCA was 76 years (IQR 70, 81), 64% were female. The estimated population incidence for people over 50 was 5.4 (95% CI 4.7, 6.1) per 100,000-person years. The female: male incidence ratio was 1.6 (95% CI 1.2, 2.2). There was no ordinal trend in GCA incidence rates by calendar year (p = 0.29). The incidence was, on average, highest in winter, but not significantly (p = 0.35). A cosinor analysis indicated no seasonal effect (p = 0.52). Conclusion The incidence of biopsy-proven GCA remains low in Australia. A higher incidence was noted compared to an earlier study. However, differences in ascertainment and methods of GCA diagnosis may have accounted for the change.